2006
DOI: 10.3201/eid1204.051614
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Ducks and H5N1 Influenza Epidemic, Thailand

Abstract: Traditional methods of raising ducks in Southeast Asia must be modified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(157 citation statements)
references
References 17 publications
4
139
0
3
Order By: Relevance
“…The statistical relationship between ducks and HPAI H5N1 virus presence and the role of ducks as reservoir has been discussed elsewhere (10,14,(20)(21)(22). However, we found a strong and consistently positive association with rice cropping intensity across epidemic waves and countries.…”
Section: Discussionsupporting
confidence: 64%
“…The statistical relationship between ducks and HPAI H5N1 virus presence and the role of ducks as reservoir has been discussed elsewhere (10,14,(20)(21)(22). However, we found a strong and consistently positive association with rice cropping intensity across epidemic waves and countries.…”
Section: Discussionsupporting
confidence: 64%
“…However, the chance of this being the cause of natural resistance in our study is unlikely because our samples were obtained from the [2004][2005] epidemics when widespread use of OTV in poultry in Thailand did not occur. The infected poultry and free-grazing birds were culled to stop the spread of the virus (Songserm et al, 2006;Walker et al, 2012). Therefore, it is pertinent to investigate these naturally occurring mutations, and in this study the focus was on the genetic diversity found outside the NA drug-binding site of H5N1 viruses collected from naturally infected Asian open-billed storks during the outbreak in 2004 From our sequencing data, three dominant quasispecies, which are the S236F, the double and the quadruple mutants, were found.…”
Section: Discussionmentioning
confidence: 99%
“…These results also suggested that post-harvest rice paddy fields, which are equally attractive to wild birds and poultry, may have actedas a meeting point between the two. With laboratory studies indicating that domestic ducks may develop HPAI H5N1 virus sub-clinical infections (Hulse-Post et al, 2005), the frequent movements of duck flocks, brought together in night shelters which are often located within villages, and from where live birds and eggs enter the market chain, made healthy ducks important potential virus transmitters and amplifiers of infection (Songserm et al, 2006).…”
Section: Introductionmentioning
confidence: 99%